Large-scale automated machine reading discovers new cancer-driving mechanisms. (26th September 2018) - Valenzuela-Escárcega, Marco A; Babur, Özgün; Hahn-Powell, Gus; Bell, Dane; Hicks, Thomas; Noriega-Atala, Enrique; Wang, Xia; Surdeanu, Mihai; Demir, Emek; Morrison, Clayton T
Abstract: PubMed, a repository and search engine for biomedical literature, now indexes >1 million articles each year. This exceeds the processing capacity of human domain experts, limiting our ability to truly understand many diseases. We present Reach, a system for automated, large-scale machine reading of biomedical papers that can extract mechanistic descriptions of biological processes with relatively high precision at high throughput. We demonstrate that combining the extracted pathway fragments with existing biological data analysis algorithms that rely on curated models helps identify and explain a large number of previously unidentified mutually exclusive altered signaling pathways in seven different cancer types. This work shows that combining human-curated 'big mechanisms' with extracted 'big data' can lead to a causal, predictive understanding of cellular processes and unlock important downstream applications.